Sistem Pakar Diagnosa Penyakit Pneumonia Menggunakan Metode Certainty Factor Pada Puskesmas Tebat Karai Kecamatan Tebat Karai Kabupaten Kepahiang - Akba, Muhammad Faisal; Sapri, Sapri; Kanedi, Indra; Hermansyah, Edy (Jurnal Media Infotama, 2025)
Pneumonia is a serious disease and can threaten human life, pneumonia is most serious when it occurs in infants and children. This study was conducted at the Tebat Karai Health Center, Tebat Karai Sub-district, Kepahiang Regency. Given the large number of patients suffering from pneumonia, sometimes the Tebat Karai Health Center has difficulty in handling it. Therefore, an expert system using the Certainty Factor method was designed. With this expert system, it can provide ease of initial consultation if the doctor is not available, although later it will still be consulted directly with the doctor. This expert system uses the PHP programming language and MySQL database. The resulting expert system can provide convenience for users to diagnose early pneumonia online.